2016
DOI: 10.1016/j.ctrv.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

New insights on PI3K/AKT pathway alterations and clinical outcomes in breast cancer

Abstract: PI3K/AKT signaling pathway plays an important role in tumorigenesis and regulates critical cellular functions including survival, proliferation and metabolism. PIK3CA mutations and AKT activation by phosphorylation (pAKT) are often detected in many cancers and especially at high frequencies in breast cancer. Mounting data suggest that PIK3CA mutations or pAKT are mostly associated with better or insignificant outcomes in estrogen receptor-positive (ER+) early stage breast cancer and tend to be with worse progn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
156
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(163 citation statements)
references
References 98 publications
5
156
1
1
Order By: Relevance
“…The PI3K/AKT/GSK-3β pathway is a classical signalling pathway in tumourigenesis [36, 37], and its activation upregulates the expression of Snail and Slug, thereby promoting EMT [20, 38, 39] and inducing the transition from G1 to S phase [40, 41]. In this study , we found that the loss of ZNF703 expression decreased the expression of p-PI3K, p-Akt, and p-GSK-3β.…”
Section: Discussionmentioning
confidence: 80%
“…The PI3K/AKT/GSK-3β pathway is a classical signalling pathway in tumourigenesis [36, 37], and its activation upregulates the expression of Snail and Slug, thereby promoting EMT [20, 38, 39] and inducing the transition from G1 to S phase [40, 41]. In this study , we found that the loss of ZNF703 expression decreased the expression of p-PI3K, p-Akt, and p-GSK-3β.…”
Section: Discussionmentioning
confidence: 80%
“…Previous studies have indicated that the Akt signaling pathway is a key factor in the viability and migration of a number of types of tumor including colorectal (32), and prostate cancer (33), and glioblastoma (34) and osteosarcoma (35). Additionally, the Akt signaling pathway is an important regulator of breast cancer (36)(37)(38). Apoptosis disorders are an additional cause for the occurrence of breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…HER family tyrosine kinase inhibitors in combination therapies) and other parallel nodal pathways (e.g. MAPK) is more effective to inhibit tumor growth and prevent emergence of regulatory feedback loops and development of drug resistance [34-36]. …”
Section: Deregulated Pi3k/akt Activation In Cancermentioning
confidence: 99%